2020
DOI: 10.17230/ad-minister.36.5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Enabling Factors for Innovation Outcomes. A Firm-Level Analysis

Abstract: Major innovation research has been primarily focused on developed countries, creating a gap in the literature related to innovation processes in emerging markets, such as Latin America. Even as some studies are aimed toward this region, their approach is usually only from the standpoint of an R&D funding perspective. This paper aims to discuss the relationship between resources for innovation and sources of innovation with innovation outcomes, using a sample of Peruvian companies, which received public fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Another relevant aspect to consider is that process innovation is significantly greater in comparison to other innovation strategies. Perhaps one explanation for this is found within the context of Peru; the main innovation outcome obtained by firms is the innovation process [92] through the acquisition of fixed assets [93]. The theoretical literature suggests that manufacturing firms seek to cope with this higher cost by introducing technological improvements, mainly in processes [94].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant aspect to consider is that process innovation is significantly greater in comparison to other innovation strategies. Perhaps one explanation for this is found within the context of Peru; the main innovation outcome obtained by firms is the innovation process [92] through the acquisition of fixed assets [93]. The theoretical literature suggests that manufacturing firms seek to cope with this higher cost by introducing technological improvements, mainly in processes [94].…”
Section: Resultsmentioning
confidence: 99%
“…We found that traditional innovation strategies, namely, product and process innovation, stand out the most in this relationship, with the process strategy being the one with the greatest statistical significance over the other strategies. This indicates that it is the most prevalent form of innovation in Peruvian manufacturing companies [93]. Hence, the process innovations allow for combining an economic and environmental gain, because they often imply cost savings linked to reduced environmental impacts, such as reduced use of materials and energy, as well as reduced waste management.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The second implication suggests that it is important for regional governments to play a crucial role as facilitators when considering integrating links between manufacturing firms (especially SMEs) and external actors (e.g. universities), and when designing science, technology and innovation policies (Seclen-Luna et al , 2020). Specifically, results call for the development of strategic partnerships with educational establishments, thus boosting training and education for product–service innovation settings (as demonstrated in H3a and H3b ).…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
“…On the other hand, although innovation efforts in Peru have increased in recent years, e.g. research and development (R&D) spending per capita increase from $4.77 in 2011 to $7.12 in 2015 (RICYT, 2017), workers’ skills are still scarce in these companies (Seclen-Luna et al , 2020). The empirical analysis is based on a large firm-level data set extracted from the National Innovation Survey in the Manufacturing Industries of Peru (ENIIM, as it its acronym is known in Spanish), with econometric regressions being used on a sample of 584 Peruvian manufacturing firms.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Ortigueira-Sánchez et al (2020) investigate what factors favor the development of the innovation capacity of Peruvian manufacturing firms. Meanwhile, Seclen-Luna, Regalado & Cordova (2020) indicate that the Peruvian government is financing innovative projects that improve the innovation capability of Peruvian manufacturing firms.…”
Section: Introductionmentioning
confidence: 99%